A deep insight into polybenzoxazole formation in the heterocycle-containing polybenzoxazine: An enlightening thought for smarter precursor design. (4th June 2021) - Liu, Jingkai; Cao, Lijun; Dai, Jinyue; Peng, Yunyan; Liu, Xiaoqing
Abstract: When artificially introducing an ortho -amide group into benzoxazine monomer, the conversion of polybenzoxazine (PBZ) into polybenzoxazole (PBO) could happen at higher temperature. However, the mechanism investigation for this reaction is far from enough, which is very significant for the PBO fabrication from PBZ. In this work, we designed three kinds of benzoxazines (PIC-abz, 4-MEP-abz and 6-MEP-abz) containing both pyridyl and amide group with similar structures. The existence of intramolecular N–H⋯N H-bonding involved with amide group and the N atom in pyridine ring, as well as the N–H⋯O H-bonding between the amide N–H and the O atom in oxazine ring, were confirmed by 1 H– 1 H nuclear overhauled effect spectroscopy (NOESY) and concentration dependent 1 H NMR spectra. In addition, the respective strength of these H-bonding in different precursors was calculated by non-covalent interaction (NCI) simulation. Results showed that besides the performance of resulted PBZ, the conversion temperature of PBZ into PBO was significantly influenced by the N–H⋯N hydrogen bonding involved with pyridyl and amide groups. Based on which, the mechanism of PBO formation was proposed and systematically investigated. The outcome of this work will help us to obtain PBO in a more efficient and reasonable manner starting from PBZ. Graphical abstract: Image 1 Highlights: Benzoxazine monomers containing both pyridyl and amide groups with similar structures were designed. The role of NH hydrogen bonding to the oxazine O atom with respect to the ease of ring opening has been supported. The role of hydrogen bonding to the PBZ-PBO transformation has been explained. Mechanism regarding intramolecular cyclization related to H-bonding strength was proposed.